ANALISIS STRATEGI BERSAING PRODUK UNSECURED LOAN PT. BANK MANDIRI (PERSERO),Tbk - , Yusuf Usamah Sepahit Lidah ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The growth of the banking industry in Indonesia is very rapid, and the eras of reform have brought many foreign banks to expand their business in Indonesia. This certainly brings the consequence that the level of competition will be very strict and severe. The Bank that survives is those which are efficient and able to continue to generate profit. Bank Mandiri has been anticipating these challenges by proclaiming that "the locomotive of growth" is in the credit sector that provides a high yield loan. One of the Bank product that provides a high yield loan is consumptive credit particularly Unsecured Loan. Therefore the unsecured loan has a very important role for Bank Mandiri in the years to come. The purpose of this thesis is to study and to identify the major factors affecting the market acceptance of the Bank Mandiri unsecured loan product, identify strengths, weaknesses and opportunities that exist in order to be utilized in achieving the target set and to evaluate the strategy of the Bank Mandiri unsecured loan product that has been obtained at this time. This study is a descriptive analytical approach using five approaches which are, Key Success Factor, Driving Forces, Porter's Competitive Strategy, Value Chain and SWOT. From this research it is known that the Bank Mandiri unsecured loans product is well known and accepted by society. It is because of the ease of the requirements, the interest rates and the fees are very competitive and also the Bank Mandiriâs reputation is very good especially during the last 5 years. The factor that must be corrected is the issue of the credit process pace that has not been uniformed and consistent in all processing branches and to better involve the Bank Mandiri branch offices to help market the unsecured loan products.